Analisis Learning Obstacle Menggunakan Pembelajaran Didaktis pada Materi Himpunan - Qanita Salma, Kamilau; Khofya Haqiqi, Arghob (Tematik : Jurnal Konten Pendidikan Matematika, 2024)
This study aims to describe the learning obstacles experienced by students in understanding the concept of set material through didactical learning approach. This type of research uses qualitative research. The research was conducted in class VII with a sample of 32 people. The data collection techniques include pretests and posttests of slices and combinations, as well as user response questionnaires by students to the didactical learning design of set material. The results of this study showed that didactical learning was able to minimize students' learning obstacles in understanding the concept of sets, namely the first learning obstacle decreased from 97% to 69% so that the first learning obstacle decreased by 28%. While the second learning obstacle decreased by 37.5%, namely from 87.5% decreased to 50%. And the third learning obstacle decreased from 34% to 19% so that the third learning obstacle decreased by 15%. Therefore, it can be concluded that didactical learning has the potential to identify and minimize learning obstacles experienced by students in understanding the concept of set material.